A new statistical approach to automated quality control in manufacturing processes. (July 2015) - Milo, Michael W.; Roan, Michael; Harris, Bradley
Highlights: Paper introduces a new approach to automated manufacturing quality control. The approach outperforms other methods, with reliable detection and low false alarm rate (∼0.1%). The sample size requirement for BPUSH is lower than comparable quality control methods. Effectiveness of the approach is shown on controlled simulated data and experimental data. Performance on experimental data is 100% True Positive Rate and 2% False Positive Rate. Abstract: Automated quality control is a key aspect of industrial maintenance. In manufacturing processes, this is often done by monitoring relevant system parameters to detect deviations from normal behavior. Previous approaches define "normalcy" as statistical distributions for a given system parameter, and detect deviations from normal by hypothesis testing. This paper develops an approach to manufacturing quality control using a newly introduced method: Bayesian Posteriors Updated Sequentially and Hierarchically (BPUSH). This approach outperforms previous methods, achieving reliable detection of faulty parts with low computational cost and low false alarm rates (∼0.1%). Finally, this paper shows that sample size requirements for BPUSH fall well below typical sizes for comparable quality control methods, achieving True Positive Rates (TPR) >99% using as few as n  = 25 samples.